Enhancing the Motivational Affordance of Information Systems: The Effects of Real-Time Performance Feedback and Goal Setting in Group Collaboration Environments - Jung, J. H.; Schneider, Christoph; Valacich, Joseph (Management Science, 2010)
Increasing globalization has created tremendous opportunities and challenges for organizations and societies. Consequently, a broad range of information technologies to better support the collaboration of diverse, and increasingly distributed, sets of participants is ever more utilized. Arguably, the success of such technology-mediated collaboration is dependent upon the quality of each individual's contributions; however, although individuals' motivations to do their best could be significantly influenced by the design of a system's human–computer interface, this area has received little attention within the context of group collaboration environments. We fill this gap by integrating research from human–computer interaction, motivation, and technology-supported group work to theoretically derive mechanisms for increasing each individual's motivation within a collective setting. Specifically, we manipulate the interface of a computer-mediated idea generation system (a widely used collaboration tool) to enhance the system's motivational affordance, i.e., the system's properties that fulfill users' motivational needs. Results from two studies demonstrate that by embedding the theoretically derived mechanisms “providing feedback” and “designing for optimal challenge” into the collaboration environment, significant performance gains were realized. The results suggest that even slight manipulations of the human–computer interface can contribute significantly to the successful design of a wide variety of group collaboration environments.